Studi Pengaruh Suhu Dan Tekanan Udara Terhadap Daya Angkat Pesawat Di Bandara S. Babullah Ternate - Akhmad Fadholi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2013)
There are three levels of operation in aviation that very important and related to meteorology. They are take off, flight (cruising), and landing. The third phase requires meteorological information. Some of meteorological elements may influence the aircraft ability at critical moments are temperature and air pressure. Temperature and pressure are two meteorological elements are interrelated, because the air pressure with temperature will determine the density of the air and the lift of aircraft. The result, at the Sultan Baabullah International Airport of Ternate suggests that the influence of temperature and air pressure is very strong. Using F-Klim 71 data from Ternate meteorological station since 1981 to 2008, air temperature has the strongest effect in March and September with 99.42% and 99.40%. The air pressure has the smallest influence March and September with 0.10% and 0.582%. The temperature with air pressure have a very strong influence with 99.99% for all of the years. Keyword: Flight, Temperature, Air pressure, Density, Lift.